CUCI NEGERI (Studi Di Dusun Saweli Kecamatan Taniwel) - Sanahu, Crison (IAKN AMBON, 2024)
Every ritual has a meaning that shapes the identity of the country's children, including Cuci Negeri. In this tradition, many meanings regarding identity and the deep essence of humanity are revealed. Washing the land is considered a sacred tradition. Cuci Negeri is not just a tradition that is carried out repeatedly every year without any depth of meaning. It is important to know the value content that continues to develop in the country, which describes the cognitive creations of the country's children resulting from empirical experiences that are never final. This research aims to analyze the process of washing the land in Sawely Hamlet, Taniwel District and to find out what values are contained in the Cuci Negeri ritual. The method used in this research is a qualitative method with observation and interview techniques. The results of this research found that the ritual of Cuci Negeri is a reflection of all planned actions and deeds that have been regulated by noble values, these values are emitted through traditional ritual procedures which are a manifestation of the community's life system, this can be understood through the stages of the ritual Cuci Negeri includes when the Cuci Negeri ritual existed, the reasons why the Cuci Negeri ritual was carried out, the problems people encountered if they did not carry out the Cuci Negeri ritual, the values in the Cuci Negeri ritual, people's views regarding the washing of the country ritual.